Perovskite nanocrystal glass and method of making the same

CN118047541BActive Publication Date: 2026-10-23SHANGHAI INST OF OPTICS & FINE MECHANICS CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410229785.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-29
Publication Date
2026-10-23
Estimated Expiration
2044-02-29

AI Technical Summary

Technical Problem

如在纳米多孔的SiO2中原位生长钙钛矿纳米晶体等,但是这种方法制备出的样品为粉末状,后续的应用我们还要进行二次处理

Benefits of technology

[0017]1.本发明使用化学气相沉积法在硅酸盐介孔玻璃中成功实现钙钛矿量子点的原位生长。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118047541B_ABST
    Figure CN118047541B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a nano-restricted growth super-stable perovskite nanocrystal glass. The super-stable perovskite nanocrystal glass is prepared by taking a silicate mesoporous glass prepared by a sol-gel method as a precursor, growing perovskite quantum dots in the mesopore of the glass by a chemical vapor deposition method, and sealing the glass. The pore size of the mesoporous glass and the size of the quantum dots are adjusted by adjusting the relative amount of aluminum lactate and tetraethyl orthosilicate in the glass precursor, so that the light emission of the quantum dots is tuned. Sealing the glass isolates the quantum dots from the external environment, greatly improving the stability of the quantum dots. The perovskite quantum dots in the nanocrystal glass prepared by the application are uniformly dispersed in the glass, and the size of the quantum dots can be adjusted. The perovskite nanocrystal glass prepared by the application has excellent light emission performance, and the quantum dots have high stability, so the application has important application value in the field of optoelectronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to perovskite nanocrystalline glass, and in particular to an ultrastable perovskite nanocrystalline glass prepared by nanoconfined growth via chemical vapor deposition. Background Technology

[0002] Perovskite nanocrystals have become a research hotspot in fields such as light-emitting displays, solar cells, and lasers due to their narrow full width at half maximum (FWHM), tunable emission, and low laser threshold. Due to quantum confinement and quantum size effects, the emission of perovskite nanocrystals can be tunable, and the emission peak position can be adjusted by changing the grain size. However, perovskite nanocrystals exposed to air are highly susceptible to decomposition. To improve the stability of perovskite nanocrystals, perovskite quantum dots are often surface passivated or encapsulated in a matrix. However, this post-synthesis process always suffers from problems such as complex procedures, long processing times, high costs, and large batch-to-batch variations.

[0003] In-situ growth of perovskite nanocrystals in a matrix has become a feasible method to improve the stability of perovskite. For example, perovskite nanocrystals can be grown in situ in nanoporous SiO2. However, the samples prepared by this method are in powder form, requiring secondary processing for subsequent applications. Another method is to prepare perovskite glass using a melt-forming process. This method involves mixing the perovskite growth source and the glass precursor together and then sintering at high temperatures. It is generally difficult to achieve a uniform distribution of perovskite nanocrystals within the glass using this method, resulting in low luminescence efficiency for perovskite nanocrystals prepared by the traditional melt-forming method. Furthermore, the melt-forming method for preparing perovskite nanocrystal glass does not allow for good control over the size of the nanocrystals.

[0004] To address the problems encountered, the inventors have developed a silicate optical mesoporous glass synthesized using the sol-gel method, and a super-stable perovskite nanocrystal glass grown in a confined environment using chemical vapor deposition. The silicate glass prepared by the sol-gel method not only possesses high transparency and excellent mechanical, chemical, and thermal properties, but also has nanoscale pore sizes, which can effectively control the size of quantum dots and prevent their aggregation. This is suitable for the in-situ confined growth of perovskite quantum dots within the pores of the mesoporous glass. Thus, by adjusting the pore size of the mesoporous glass, the size of the quantum dots can be controlled, thereby achieving the modulation of the quantum dot emission wavelength. More importantly, the mesopores of silicate glass collapse at high temperatures. After quantum dot growth, the pore size of the mesoporous glass can be collapsed by increasing the temperature, thereby completely isolating the prepared perovskite nanocrystals from the external environment and greatly improving their stability. This invention provides a new method for preparing perovskite nanocrystal glass. This method is simple, low-cost, and produces perovskite nanocrystal glass with uniformity, tunable emission, and super-stability, making it important for applications in optoelectronic devices such as light-emitting diodes. Summary of the Invention

[0005] The purpose of this invention is to provide an ultra-stable perovskite nanocrystalline glass prepared by nanoconfined growth using chemical vapor deposition (CVD). Using a silicate mesoporous glass as a carrier, and through the adjustment of a series of preparation parameters, in-situ growth and pore sealing of perovskite nanocrystals of different sizes and types are achieved within the silicate mesoporous glass via CVD, resulting in an ultra-stable perovskite nanocrystalline glass with tunable luminescence.

[0006] The technical solution of the present invention is as follows:

[0007] Ultrastable perovskite nanocrystalline glass was prepared by nanoconfined growth via chemical vapor deposition. The nanocrystals are perovskite quantum dots with the structural formula ABO3 (A = Cs, B = Pb, Sn, O = Cl, Br, I). The silicate mesoporous glass is a xAl2O3-(100-x)SiO2 sol-gel mesoporous glass with a specific surface area greater than 400 m² / g. 2 / g, with an average pore diameter ranging from 1.0 to 5.0 nm. The ultrastable perovskite nanocrystalline glass prepared by the above chemical vapor deposition method for nanoconfined growth is characterized by comprising two parts: sol-gel preparation of silicate mesoporous glass and in-situ growth of perovskite quantum dots followed by pore sealing. The steps include:

[0008] (1) Using tetraethyl orthosilicate and aluminum lactate as precursors; water and ethanol as solvents;

[0009] (2) At room temperature, tetraethyl orthosilicate is dissolved in ethanol solvent and aluminum lactate is dissolved in water. They are stirred evenly separately and then mixed. The molar ratio of the precursors is Al2O3:SiO2=x:(100-x). The mixture is stirred evenly to obtain a mixed solution.

[0010] (3) Transfer the mixed solution to a covered petri dish and let it stand at room temperature for 12 hours to obtain a silicate sol;

[0011] (4) The silicate sol is placed in an oven and dried at a temperature of 50~100℃. It is kept at 50, 60, 70, 80 and 90℃ for 12 hours respectively, and finally kept at 100℃ for 4 hours to obtain silicate dry gel.

[0012] (5) The silicate dry gel is placed in a crucible and sintered in a muffle furnace. The sintering temperature range is 200~700℃, the heating rate is 1℃ / min, and the temperature is kept at 200, 400, 600 and 700℃ for 4 hours respectively. Finally, it is cooled to room temperature to obtain colorless and transparent silicate mesoporous glass.

[0013] (6) In-situ growth and sealing of perovskite nanocrystals: In-situ growth and sealing of perovskite nanocrystal glass were carried out in a tube furnace. The perovskite growth source was placed in the heating center of the tube furnace, and the silicate mesoporous glass was placed 15 cm downstream of the heating center. High-purity argon was used as the protective gas and carrier gas. The reaction temperature was 500~600℃. After the perovskite nanocrystal growth was completed, the temperature was raised to 900℃ and held for 120 min.

[0014] (7) After the reaction is complete, perovskite nanocrystal glass is obtained.

[0015] The perovskite growth sources in step (6) include: PbCl2, CsCl, PbBr2, SnBr2, CsBr, PbI2, SnI, and CsI.

[0016] This invention has the following innovative features compared to existing technologies:

[0017] 1. This invention successfully achieves in-situ growth of perovskite quantum dots in silicate mesoporous glass using chemical vapor deposition.

[0018] 2. This invention utilizes the characteristic of the pore size of silicate mesoporous glass to collapse at high temperatures, thereby achieving pore sealing of perovskite quantum dot glass while maintaining the excellent performance and structure of perovskite nanocrystals, and preparing ultra-stable perovskite nanocrystal glass.

[0019] 3. This invention utilizes the adjustable pore size of silicate mesoporous glass to control the size of quantum dots, thereby achieving adjustment of the emission wavelength of quantum dots. Attached Figure Description

[0020] Figure 1 Photograph of the prepared perovskite nanocrystal glass under fluorescent light;

[0021] Figure 2 The BET test spectra of the silicate mesoporous glasses prepared in Examples 1-8 are shown.

[0022] Figure 3 The BET spectrum of the perovskite nanocrystal glass prepared in Example 3;

[0023] Figure 4 The TEM image of the perovskite nanocrystal glass prepared in Example 3;

[0024] Figure 5 The absorption spectrum of the perovskite nanocrystal glass prepared in Example 3;

[0025] Figure 6 The emission spectra of perovskite nanocrystal glasses prepared in Examples 1-8 under light excitation at a wavelength of 350 nm are shown.

[0026] Figure 7 The emission spectra of perovskite nanocrystal glasses prepared in Examples 9-10 under light excitation at a wavelength of 350 nm are shown.

[0027] Figure 8 The emission spectrum of the perovskite nanocrystal glass prepared in Example 11 under light excitation at a wavelength of 350 nm;

[0028] Figure 9 The emission spectrum of perovskite nanocrystal glass prepared in Example 12 under light excitation at a wavelength of 350 nm;

[0029] Figure 10 The image shows the stability test spectrum of the perovskite nanocrystal glass prepared in Example 5 when immersed in water. Detailed Implementation

[0030] The present invention will be further illustrated below with reference to specific embodiments. It is important to note that these embodiments are for illustrative purposes only and should not be construed as limiting the scope of protection of the invention. Those skilled in the art can make non-essential improvements and adjustments based on the above description of the invention. Test methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer.

[0031] The sources, names, and specifications of the experimental materials or instruments used in the embodiments of this invention are shown in the table below:

[0032]

[0033] Table 1: List of experimental materials used in this invention

[0034] The present invention will be further described below with reference to embodiments, but these should not be construed as limiting the scope of protection of the present invention.

[0035]

[0036] Table 2: Statistical analysis of emission wavelengths from glass samples with the same quantum dots but different pore sizes

[0037]

[0038] Table 3: Statistics on emission wavelengths of samples of different types of quantum dots with the same aperture in glass

[0039] Example 1:

[0040] The preparation method of Example 1 is as follows:

[0041] (1) Precursor preparation: At room temperature, 1.34 ml of tetraethyl orthosilicate (SiC8H) was added. 20 O4) dissolved in ethanol solvent, 0.019g aluminum lactate (C9H) 15 AlO9) is dissolved in water, stirred separately until homogeneous, and then mixed. The precursor molar ratio is Al2O3:SiO2 = 0.5:99.5. After stirring until homogeneous, a mixed solution is obtained. Here, we can control the pore size of the mesoporous glass by controlling the molar ratio of the precursor, and thus control the size of the quantum dots, thereby achieving the tuning of the luminescence of the quantum dots.

[0042] (2) Preparation of silicate mesoporous glass: The mixed solution was transferred to a covered petri dish and left to stand at room temperature for 12 hours to obtain silicate sol; the silicate sol was placed in an oven to dry at a temperature of 50~100℃, and kept at 50, 60, 70, 80 and 90℃ for 2 hours respectively, and finally kept at 100℃ for 4 hours to obtain silicate dry gel; the silicate dry gel was placed in a crucible and sintered in a muffle furnace at a temperature range of 200~700℃ and a heating rate of 1℃ / min, and kept at 200, 400, 600 and 700℃ for 4 hours respectively, and finally cooled to room temperature to obtain colorless and transparent silicate mesoporous glass;

[0043] (3) In-situ growth and sealing of perovskite nanocrystals: A mixed source of PbBr2 and CsBr with a molar ratio of 1:1 was placed in the heating center of a tube furnace, and a silicate mesoporous glass was placed 15 cm downstream of the heating center. High-purity argon was used as a protective gas and a carrier gas, and the reaction temperature was 550℃. The chemical reaction formula was PbBr2 + CsBr → CsPbBr3. After the perovskite nanocrystals were grown, the temperature was raised to 900℃ and the holding time was 120 min.

[0044] Test Example 1: Glass Nanopore Performance Testing

[0045] Test sample: Mesoporous silicate glass prepared in Example 1

[0046] Test equipment: Nitrogen adsorption-desorption apparatus (Autosorb iQ, Anton Paar, Austria);

[0047] The transparent nanoporous glass prepared in Example 1 has an average pore size of 1.4 nm, as shown below. Figure 2 As shown in a;

[0048] Test Example 2: Sample Photoluminescence Test

[0049] Test sample: Perovskite nanocrystal glass prepared in Example 1

[0050] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0051] This perovskite nanocrystal glass emits light with a wavelength of 473 nm when excited by 350 nm light, such as Figure 6 As shown in curve a.

[0052] Example 2:

[0053] The preparation method of Example 2 is as follows:

[0054] (1) Precursor preparation: At room temperature, 1.34 ml of tetraethyl orthosilicate (SiC8H) was added. 20 O4) dissolved in ethanol solvent, 0.038g aluminum lactate (C9H) 15 AlO9) is dissolved in water, stirred evenly separately, and then mixed. The precursor molar ratio is Al2O3:SiO2 = 1:99. After stirring evenly, a mixed solution is obtained. Here, we can control the pore size of the mesoporous glass by controlling the molar ratio of the precursor, and thus control the size of the quantum dots, thereby achieving the tuning of the luminescence of the quantum dots.

[0055] (2) Preparation of silicate mesoporous glass: Repeat step (2) of Example 1;

[0056] (3) In-situ growth and sealing of perovskite nanocrystals: Repeat step (3) of Example 1.

[0057] Test Example 3: Glass Nanopore Performance Testing

[0058] Test sample: Mesoporous silicate glass prepared in Example 2

[0059] Test equipment: Nitrogen adsorption-desorption apparatus (Autosorb iQ, Anton Paar, Austria);

[0060] The transparent nanoporous glass prepared in Example 2 has an average pore size of 1.6 nm, as shown below. Figure 2 As shown in b;

[0061] Test Example 4: Sample Photoluminescence Test

[0062] Test sample: Perovskite nanocrystal glass prepared in Example 2

[0063] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0064] This perovskite nanocrystal glass emits light with a wavelength of 491 nm when excited by 350 nm light, such as Figure 6 As shown in curve b.

[0065] Example 3:

[0066] The preparation method of Example 3 is as follows:

[0067] (1) Precursor preparation: At room temperature, 1.34 ml of tetraethyl orthosilicate (SiC8H) was added. 20 O4) dissolved in ethanol solvent, 0.19g aluminum lactate (C9H) 15 AlO9) is dissolved in water, stirred separately until homogeneous, and then mixed. The precursor molar ratio is Al2O3:SiO2 = 5:95. After stirring until homogeneous, a mixed solution is obtained. Here, we can control the pore size of the mesoporous glass by controlling the molar ratio of the precursor, and thus control the size of the quantum dots, thereby achieving the tuning of the luminescence of the quantum dots.

[0068] (2) Preparation of silicate mesoporous glass: Repeat step (2) of Example 1;

[0069] (3) In-situ growth and sealing of perovskite nanocrystals: Repeat step (3) of Example 1.

[0070] Test Example 5: Glass Nanopore Performance Testing

[0071] Test sample: Mesoporous silicate glass prepared in Example 3

[0072] Test equipment: Nitrogen adsorption-desorption apparatus (Autosorb iQ, Anton Paar, Austria);

[0073] The transparent nanoporous glass prepared in Example 3 has an average pore size of 2.6 nm. Figure 2 As shown in c;

[0074] Test Example 6: Nanopore Performance Testing of Perovskite Nanocrystalline Glass

[0075] Test sample: Perovskite nanocrystalline glass prepared in Example 3

[0076] Test equipment: Nitrogen adsorption-desorption apparatus (Autosorb iQ, Anton Paar, Austria);

[0077] The perovskite nanocrystalline glass prepared in Example 3 does not have mesoporous properties, such as Figure 3 As shown;

[0078] Test Example 7: Perovskite Distribution Test in Glass

[0079] Test sample: Perovskite nanocrystalline glass prepared in Example 3

[0080] Testing equipment: Transmission electron microscope (HEOL-2010, USA);

[0081] In the perovskite nanocrystalline glass prepared in Example 3, perovskite quantum dots are uniformly distributed within the glass, such as... Figure 4 As shown;

[0082] Test Example 8: Sample Photoluminescence Test

[0083] Test sample: Perovskite nanocrystal glass prepared in Example 3

[0084] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0085] This perovskite nanocrystal glass emits light with a wavelength of 494 nm when excited by 350 nm light, such as Figure 6 As shown in curve c;

[0086] Test Example 9: Sample Absorption Characteristics Test

[0087] Test sample: Perovskite nanocrystal glass prepared in Example 3

[0088] Testing equipment: UV-Vis spectrophotometer (AMBDA 750, PerkinElmer, USA); Testing range: 200-800nm;

[0089] This perovskite nanocrystal glass exhibits a distinct absorption peak at 490 nm, as shown in the curve. Figure 5 As shown;

[0090] Test Example 10: Sample Stability Test

[0091] Test sample: Perovskite nanocrystal glass prepared in Example 3

[0092] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0093] The sample was immersed in water to test the change in its luminescence intensity. It was found that the sample remained stable in water, and the quantum dots did not quench. This indicates that the prepared nanocrystalline glass has high stability. The test results are as follows: Figure 10 As shown.

[0094] Example 4:

[0095] The preparation method of Example 4 is as follows:

[0096] (1) Precursor preparation: At room temperature, 1.34 ml of tetraethyl orthosilicate (SiC8H) was added. 20 O4) is dissolved in ethanol solvent, 0.32g of aluminum lactate (C9H) 15 AlO9) is dissolved in water, stirred separately until homogeneous, and then mixed. The precursor molar ratio is Al2O3:SiO2 = 8:92. After stirring until homogeneous, a mixed solution is obtained. Here, we can control the pore size of the mesoporous glass by controlling the molar ratio of the precursor, and thus control the size of the quantum dots, thereby achieving the tuning of the luminescence of the quantum dots.

[0097] (2) Preparation of silicate mesoporous glass: Repeat step (2) of Example 1;

[0098] (3) In-situ growth and sealing of perovskite nanocrystals: Repeat step (3) of Example 1.

[0099] Test Example 11: Performance Testing of Glass Nanopores

[0100] Test sample: Mesoporous silicate glass prepared in Example 4

[0101] Test equipment: Nitrogen adsorption-desorption apparatus (Autosorb iQ, Anton Paar, Austria);

[0102] The transparent nanoporous glass prepared in Example 2 has an average pore size of 3.8 nm, as shown below. Figure 2 As shown in d;

[0103] Test Example 12: Sample Photoluminescence Test

[0104] Test sample: Perovskite nanocrystal glass prepared in Example 2

[0105] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0106] This perovskite nanocrystal glass emits light with a wavelength of 496 nm when excited by 350 nm light, such as Figure 6 As shown by curve d.

[0107] Example 5:

[0108] The preparation method of Example 5 is as follows:

[0109] (1) Precursor preparation: At room temperature, 1.34 ml of tetraethyl orthosilicate (SiC8H) was added. 20 O4) dissolved in ethanol solvent, 0.38g aluminum lactate (C9H) 15 AlO9) is dissolved in water, stirred separately until homogeneous, and then mixed. The precursor molar ratio is Al2O3:SiO2 = 10:90. After stirring until homogeneous, a mixed solution is obtained. Here, we can control the pore size of the mesoporous glass by controlling the molar ratio of the precursor, and thus control the size of the quantum dots, thereby achieving the tuning of the luminescence of the quantum dots.

[0110] (2) Preparation of silicate mesoporous glass: Repeat step (2) of Example 1;

[0111] (3) In-situ growth and sealing of perovskite nanocrystals: Repeat step (3) of Example 1.

[0112] Test Example 13: Performance Testing of Glass Nanopores

[0113] Test sample: Mesoporous silicate glass prepared in Example 5

[0114] Test equipment: Nitrogen adsorption-desorption apparatus (Autosorb iQ, Anton Paar, Austria);

[0115] The transparent nanoporous glass prepared in Example 5 has an average pore size of 4.0 nm. Figure 2 As shown in e;

[0116] Test Example 14: Sample Photoluminescence Test

[0117] Test sample: Perovskite nanocrystal glass prepared in Example 5

[0118] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0119] This perovskite nanocrystal glass emits light with a wavelength of 499 nm when excited by 350 nm light, such as Figure 6 As shown by curve e.

[0120] Example 6:

[0121] The preparation method of Example 6 is as follows:

[0122] (1) Precursor preparation: At room temperature, 1.34 ml of tetraethyl orthosilicate (SiC8H) was added. 20 O4) is dissolved in ethanol solvent, 0.58g of aluminum lactate (C9H) 15 AlO9) is dissolved in water, stirred separately until homogeneous, and then mixed. The precursor molar ratio is Al2O3:SiO2 = 13:87. After stirring until homogeneous, a mixed solution is obtained. Here, we can control the pore size of the mesoporous glass by controlling the molar ratio of the precursor, and thus control the size of the quantum dots, thereby achieving the tuning of the luminescence of the quantum dots.

[0123] (2) Preparation of silicate mesoporous glass: Repeat step (2) of Example 1;

[0124] (3) In-situ growth and sealing of perovskite nanocrystals: Repeat step (3) of Example 1.

[0125] Test Example 15: Performance Testing of Glass Nanopores

[0126] Test sample: Mesoporous silicate glass prepared in Example 6

[0127] Test equipment: Nitrogen adsorption-desorption apparatus (Autosorb iQ, Anton Paar, Austria);

[0128] The transparent nanoporous glass prepared in Example 2 has an average pore size of 4.2 nm, as shown below. Figure 2 As shown in f.

[0129] Test Example 16: Sample Photoluminescence Test

[0130] Test sample: Perovskite nanocrystal glass prepared in Example 6

[0131] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0132] This perovskite nanocrystal glass emits light with a wavelength of 506 nm when excited by 350 nm light, such as Figure 6 As shown by curve f.

[0133] Example 7:

[0134] The preparation method of Example 7 is as follows:

[0135] (1) Precursor preparation: At room temperature, 1.34 ml of tetraethyl orthosilicate (SiC8H) was added. 20 O4) dissolved in ethanol solvent, 0.78g aluminum lactate (C9H) 15 AlO9) is dissolved in water, stirred separately until homogeneous, and then mixed. The precursor molar ratio is Al2O3:SiO2 = 17:83. After stirring until homogeneous, a mixed solution is obtained. Here, we can control the pore size of the mesoporous glass by controlling the molar ratio of the precursor, and thus control the size of the quantum dots, thereby achieving the tuning of the luminescence of the quantum dots.

[0136] (2) Preparation of silicate mesoporous glass: Repeat step (2) of Example 1;

[0137] (3) In-situ growth and sealing of perovskite nanocrystals: Repeat step (3) of Example 1.

[0138] Test Example 17: Performance Testing of Glass Nanopores

[0139] Test sample: Mesoporous silicate glass prepared in Example 7

[0140] Test equipment: Nitrogen adsorption-desorption apparatus (Autosorb iQ, Anton Paar, Austria);

[0141] The transparent nanoporous glass prepared in Example 2 has an average pore size of 4.5 nm, as shown below. Figure 2 As shown in g;

[0142] Test Example 18: Sample Photoluminescence Test

[0143] Test sample: Perovskite nanocrystal glass prepared in Example 7

[0144] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0145] This perovskite nanocrystal glass emits light with a wavelength of 510 nm when excited by 350 nm light, such as Figure 6 As shown by curve g.

[0146] Example 8:

[0147] The preparation method of Example 8 is as follows:

[0148] (1) Precursor preparation: At room temperature, 1.34 ml of tetraethyl orthosilicate (SiC8H) was added. 20 O4) dissolved in ethanol solvent, 1.27g aluminum lactate (C9H) 15AlO9) is dissolved in water, stirred separately until homogeneous, and then mixed. The precursor molar ratio is Al2O3:SiO2 = 25:75. After stirring until homogeneous, a mixed solution is obtained. Here, we can control the pore size of the mesoporous glass by controlling the molar ratio of the precursor, and thus control the size of the quantum dots, thereby achieving the tuning of the luminescence of the quantum dots.

[0149] (2) Preparation of silicate mesoporous glass: Repeat step (2) of Example 1;

[0150] (3) In-situ growth and sealing of perovskite nanocrystals: Repeat step (3) of Example 1.

[0151] Test Example 19: Performance Testing of Glass Nanopores

[0152] Test sample: Mesoporous silicate glass prepared in Example 8

[0153] Test equipment: Nitrogen adsorption-desorption apparatus (Autosorb iQ, Anton Paar, Austria);

[0154] The transparent nanoporous glass prepared in Example 2 has an average pore size of 4.9 nm, as shown below. Figure 2 As shown in h;

[0155] Test Example 20: Sample Photoluminescence Test

[0156] Test sample: Perovskite nanocrystal glass prepared in Example 8

[0157] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0158] This perovskite nanocrystal glass emits light with a wavelength of 516 nm when excited by 350 nm light, such as Figure 6 As shown by curve g.

[0159] Example 9:

[0160] The preparation method of Example 9 is as follows:

[0161] (1) Precursor preparation: At room temperature, tetraethyl orthosilicate (SiC8H) was prepared. 20 O4) dissolves in ethanol solvent, aluminum lactate (C9H) 15 AlO9) was dissolved in water, and the mixtures were stirred separately until homogeneous. Then they were mixed together, with the precursor molar ratio being Al2O3:SiO2 = 5:95. The mixture was stirred until homogeneous to obtain a mixed solution.

[0162] (2) Preparation of silicate mesoporous glass: Repeat step (2) of Example 1;

[0163] (3) In-situ growth and sealing of perovskite nanocrystals: A 1:1 molar ratio of PbCl2 and CsBr was placed in the heating center of a tube furnace. A silicate mesoporous glass was placed 15 cm downstream of the heating center. High-purity argon was used as both a protective gas and a carrier gas. The reaction temperature was 600 °C. The chemical reaction was PbCl2 + CsBr → CsPbBr y Cl 3-y After the perovskite nanocrystals have grown, the temperature is raised to 900℃ and held for 120 minutes.

[0164] Test Example 21: Sample Photoluminescence Test

[0165] Test sample: Perovskite nanocrystal glass prepared in Example 9

[0166] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0167] This perovskite nanocrystal glass emits light with a wavelength of 450 nm when excited by 350 nm light, such as Figure 7 As shown in curve a.

[0168] Example 10:

[0169] The preparation method of Example 10 is as follows:

[0170] (1) Precursor preparation: At room temperature, tetraethyl orthosilicate (SiC8H) was prepared. 20 O4) dissolves in ethanol solvent, aluminum lactate (C9H) 15 AlO9) was dissolved in water, and the mixtures were stirred separately until homogeneous. Then they were mixed together, with the precursor molar ratio being Al2O3:SiO2 = 5:95. The mixture was stirred until homogeneous to obtain a mixed solution.

[0171] (2) Preparation of silicate mesoporous glass: Repeat step (2) of Example 1;

[0172] (3) In-situ growth and sealing of perovskite nanocrystals: A mixed source of PbBr2 and CsI with a molar ratio of 1:1 was placed in the heating center of a tube furnace. The silicate mesoporous glass was placed 15 cm downstream of the heating center. High-purity argon was used as the protective gas and carrier gas. The reaction temperature was 550℃. The chemical reaction formula was PbCl2 + CsBr → CsPbI y Br 3-y After the perovskite nanocrystals have grown, the temperature is raised to 900℃ and held for 120 minutes.

[0173] Test Example 22: Sample Photoluminescence Test

[0174] Test sample: Perovskite nanocrystal glass prepared in Example 10

[0175] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0176] This perovskite nanocrystal glass emits wavelengths of 566 nm when excited by 350 nm light, such as Figure 7 As shown in curve b.

[0177] Example 11:

[0178] The preparation method of Example 11 is as follows:

[0179] (1) Precursor preparation: Repeat step (1) of Example 10;

[0180] (2) Preparation of silicate mesoporous glass: Repeat step (2) of Example 1;

[0181] (3) In-situ growth and sealing of perovskite nanocrystals: A mixed source of SnBr2 and CsBr with a molar ratio of 1:1 was placed in the heating center of a tube furnace, and a silicate mesoporous glass was placed 15 cm downstream of the heating center. High-purity argon was used as a protective gas and a carrier gas, and the reaction temperature was 550℃. The chemical reaction formula was SnBr2+CsBr→CsSnBr3. After the perovskite nanocrystals were grown, the temperature was raised to 900℃ and the holding time was 120 min.

[0182] Test Example 23: Sample Photoluminescence Test

[0183] Test sample: Perovskite nanocrystal glass prepared in Example 11

[0184] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0185] This perovskite nanocrystal glass emits wavelengths of 620 nm when excited by 350 nm light, such as Figure 8 As shown.

[0186] Example 12:

[0187] The preparation method of Example 12 is as follows:

[0188] (1) Precursor preparation: Repeat step (1) of Example 10;

[0189] (2) Preparation of silicate mesoporous glass: Repeat step (2) of Example 1;

[0190] (3) In-situ growth and sealing of perovskite nanocrystals: A mixed source of SnI2 and CsI with a molar ratio of 1:1 was placed in the heating center of a tube furnace. The silicate mesoporous glass was placed 15 cm downstream of the heating center. High-purity argon was used as the protective gas and carrier gas. The reaction temperature was 500℃. The chemical reaction formula was SnI2+CsI→CsSnI3. After the perovskite nanocrystals were grown, the temperature was raised to 900℃ and the holding time was 120 min.

[0191] Test Example 24: Sample Photoluminescence Test

[0192] Test sample: Perovskite nanocrystal glass prepared in Example 12

[0193] Testing equipment: Edinburgh fluorescence spectrometer (FLS1000); testing range 400-800 nm;

[0194] This perovskite nanocrystal glass emits wavelengths of 700 nm when excited by 350 nm light, such as Figure 9 As shown.

Claims

1. A method for preparing perovskite nanocrystalline glass, wherein the nanocrystalline material is perovskite quantum dots with the structural formula ABO3, wherein A is Cs, B is Pb / Sn, and O is Cl / Br / I, characterized in that... This method comprises two parts: the preparation of silicate mesoporous glass by sol-gel method as follows (1) to (4), the in-situ growth of perovskite nanocrystals by chemical vapor deposition, and the sealing of the nanopores of the mesoporous glass as follows (5). The specific steps are as follows: (1) Using tetraethyl orthosilicate and aluminum lactate as precursors; water and ethanol as solvents; at room temperature, the precursor tetraethyl orthosilicate is dissolved in ethanol, and the precursor aluminum lactate is dissolved in water. The solutions are stirred separately until homogeneous, then mixed and stirred until homogeneous to obtain a mixed solution. The molar ratio of the precursors is Al2O3:SiO2 = x:(100-x), where x≦25, and the specific surface area is greater than 400 m². 2 / g, with an average pore diameter ranging from 1.0 to 5.0 nm; (2) Transfer the mixed solution to a covered petri dish and let it stand at room temperature for 12 hours to obtain a silicate sol; (3) The silicate sol is placed in an oven to dry at a temperature of 50~100℃. It is kept at 50, 60, 70, 80 and 90℃ respectively, and finally kept at 100℃ and cooled to room temperature to obtain silicate dry gel. (4) The silicate dry gel is placed in a crucible and sintered in a muffle furnace. The sintering temperature range is 200~700℃. The temperature is gradually increased, and the temperature is maintained at 200, 400, 600 and 700℃ respectively. Finally, it is cooled to room temperature to obtain colorless and transparent silicate mesoporous glass. (5) In-situ growth and sealing of perovskite nanocrystal glass were carried out in a tube furnace. The perovskite growth source was placed in the heating center of the tube furnace, and the silicate mesoporous glass was placed in the tube furnace. High-purity argon was used as the protective gas and carrier gas. The reaction temperature was 500~600℃. After the perovskite nanocrystal growth was completed, the temperature was raised to 900℃ and kept at that temperature. Finally, it was cooled to room temperature to obtain perovskite nanocrystal glass.

2. The method for preparing a perovskite nanocrystalline glass according to claim 1, characterized in that, The perovskite quantum dot growth sources in step (5) include: PbCl2, CsCl, PbBr2, SnBr2, CsBr, PbI2, SnI, and CsI.

3. The method for preparing a perovskite nanocrystalline glass according to claim 1, characterized in that, The heat preservation operation in step (3) is for 4 hours; the gradual heating rate in step (4) is 1℃ / min, and the heat preservation operation in step (4) is for 4 hours; the heat preservation operation in step (5) is for 120 minutes.

4. The method for preparing a perovskite nanocrystal glass according to claim 1, wherein the nanocrystal is CsPbBr3, and the perovskite quantum dot growth source in step (5) includes: PbBr2+CsBr; the precursor Al2O3:SiO2 molar ratio is 0.5:99.5~25:75; The invention is characterized in that, as the content of the precursor Al2O3:SiO2 increases, the nanopore size of the silicate mesoporous glass also increases, with the nanopore size ranging from 1.4 nm to 4.9 nm and the perovskite quantum dot emission wavelength ranging from 472 nm to 516 nm.

5. The method for preparing a perovskite nanocrystal glass according to claim 1, wherein the nanocrystal is CsBO3, B is Pb / Sn, O is Cl / Br / I, and the perovskite quantum dot growth source in step (5) includes: The precursors are PbCl2, PbBr2, SnBr2, CsBr, SnI, and CsI; the molar ratio of Al2O3 to SiO2 is 5:95; and the perovskite quantum dots emit light in the range of 450 nm to 700 nm.

6. A perovskite nanocrystalline glass prepared by any one of the preparation methods according to claims 1-5, characterized in that, Perovskite nanocrystals are generated using a silicate mesoporous glass as a carrier and halides as the growth source for perovskite quantum dots via chemical vapor deposition (CVD). The CVD process involves in-situ growth and sealing of the perovskite nanocrystals in a tube furnace. The perovskite growth source is placed in the heating center of the tube furnace, and the silicate mesoporous glass is placed inside the furnace. High-purity argon is used as both the protective and carrier gas. The perovskite nanocrystal glass exhibits silicate mesoporous channel collapse on both its inner and outer surfaces. The silicate mesoporous glass is an aluminosilicate mesoporous glass.

7. The perovskite nanocrystalline glass as described in claim 6, characterized in that, The surface of the perovskite nanocrystals is covered by the silicate mesoporous glass, and the perovskite nanocrystals are encapsulated within the nanopores of the silicate mesoporous glass.

8. The perovskite nanocrystalline glass as described in claim 6, characterized in that, By changing the Al2O3:SiO2 molar ratio of the precursor of the silicate mesoporous glass or changing the growth source of the perovskite quantum dots, the nanopore size of the silicate mesoporous glass can be changed, thereby controlling the size of the perovskite quantum dots.

Citation Information

Patent Citations

  • Preparation method of semiconductor nanocrystalline fluorescent material, semiconductor nanocrystalline fluorescent material prepared by method and application of semiconductor nanocrystalline fluorescent material

    CN110734758A

  • Preparation method and application of perovskite mesoporous glass

    CN115196883A

  • Method for growing halide perovskite nanocrystals through in-situ chemical vapor deposition

    CN115261979A

  • Afterglow luminescent carbon quantum dot porous glass and preparation method thereof

    CN119930158A